Abstracts in social gerontology. - National Council on the Aging (Newbury Park, Calif. Sage Periodicals Press, 1993)
Classified arrangement of literature consisting of "books, articles, pamphlets, government publications, legislative research studies, as well as other fugitive material." Entries give biographical information, keywords, and abstracts. Also contains a section on related citations. Author and subject indexes.
"Published in cooperation with the National Council on the Aging, Inc."
Keywords: Gerontology -- Abstracts -- Periodicals; Aging -- Abstracts -- Periodicals